2015
DOI: 10.1111/jpim.12286
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Customer Codevelopment of New Products: The Moderating Effects of Utilitarian and Hedonic Radicalness

Abstract: There is growing belief in the value of actively involving customers in innovation, commonly referred to as customer codevelopment or cocreation. These strategies are generally believed to be beneficial, although contingent views are prevalent. A widely espoused contingent view is that the positive contribution of customer codevelopment is dependent on the degree of radicalness (or innovativeness) of the products being developed. Some work argues that customer codevelopment is more useful for incremental innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 101 publications
(186 reference statements)
0
26
0
Order By: Relevance
“…Originating from strategic management (e.g., Normann & Ramirez, 1993;Prahalad & Ramaswamy, 2000), the concept has become strongly linked to service marketing (e.g., Vargo & Lush, 2004), where studies mostly focus on the usage stage and co-creation of value in use (e.g., Vargo et al, 2008). Recently, cocreation has also stimulated increased interest in innovation and new product development literature (e.g., Lau, Tang, & Yam, 2010;Mahr et al, 2014), with focus on how firms can involve customers in co-development work (e.g., Candi, Van den Ende, & Gemser, 2016;Kleinsmann et al, 2010). From a project management perspective, it is notable that the production stage is often left out in these broad literature sets.…”
Section: Co-creation Of Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Originating from strategic management (e.g., Normann & Ramirez, 1993;Prahalad & Ramaswamy, 2000), the concept has become strongly linked to service marketing (e.g., Vargo & Lush, 2004), where studies mostly focus on the usage stage and co-creation of value in use (e.g., Vargo et al, 2008). Recently, cocreation has also stimulated increased interest in innovation and new product development literature (e.g., Lau, Tang, & Yam, 2010;Mahr et al, 2014), with focus on how firms can involve customers in co-development work (e.g., Candi, Van den Ende, & Gemser, 2016;Kleinsmann et al, 2010). From a project management perspective, it is notable that the production stage is often left out in these broad literature sets.…”
Section: Co-creation Of Valuementioning
confidence: 99%
“…Two issues stick out as having an effect on the outcomes: (1) the type of learning mode and (2) the timing of the co-creation practices. In terms of the type of learning mode, several studies show that customer involvement in co-development is especially important in achieving exploration (e.g., Candi et al, 2016;Lettl, 2007), whereas others have found that tight couplings with the customer enhances exploitation (e.g., Andriopoulos & Lewis, 2009). In terms of the timing of co-creation practices, the common argument is that customers should be involved either early in the design stage to provide input to the co-development work, or at the implementation stage to learn how to use the finalized product.…”
Section: Co-creation Of Valuementioning
confidence: 99%
“…Hirschman's argument here is analogous to the distinction recently put forward byCandi et al (2016) in their study about customer codevelopment of new products, where authors differentiate innovation along utilitarian and hedonic radicalness. The symbolic attribute raised by Hirschman is also tangent to the concept of stylistic innovation where changes in the aesthetic characteristics can generate a new meaning arising from the consumption of an already existent product(Cappetta et al, 2006).…”
mentioning
confidence: 72%
“…However, they find that the value of the customer as an information source in the early stage is greater when the innovation level is low. More recently, Candi et al (2015) argue that the role of customer as a co-creator of value is lower for innovations that address sentiments or emotions (hedonic radicalness) and higher for innovations that address specific functionality needs (utilitarian radicalness).…”
Section: Conceptual Frameworkmentioning
confidence: 99%